I. V. Oxytocin versus oral Misoprostol for augmentation of labour, associated complications and effect on neonatal wellbeing - Wilson, Swapnil; Das, Subrata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The complications of prolonged labor are well recognized and the caesarean section has been used liberally. But even then, prolonged labor continues to be a problem. This could be due to weak uterine contractions or poor cervical dilatation. The problem can be overcome with the use of oxytocic drugs. The aim of the study was to compare the efficacy, adverse effects, safety, and feto-maternal outcome of the ARM and oral misoprostol with Artificial Rupture of Membrane (ARM) and oxytocin infusion for labor augmentation. Methods: This prospective study was conducted in the labor room of NRS Medical College and Hospital Kolkata and included 100 primigravidae women carrying singleton pregnancy at term with spontaneous onset of labor. Results: The result findings of the present study show that the prolonged labor was the major indication for LSCS in both the groups. There was a significantly higher subjects (P <0.05*) had fetal distress or fetal bradycardia, meconium staining of liquor, Tachysystole in the misoprostol group, compared to oxytocin group. No significant difference was observed among the groups with respect to neonatal wellbeing. Conclusions: Both the agents i.e. oral misoprostol and I.V. oxytocin shortens the duration of labor effectively and are effective for augmentation of labor. Apart from Tachysystole and meconium staining of liquor and fetal distress the incidence of any other complication was not significantly more in the oral misoprostol group when compared with oxytocin group. Status of the neonate was almost similar in both the groups.